2010
DOI: 10.1111/j.1747-0803.2010.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Percutaneous Closure of a Secundum Atrial Septal Defect through Femoral Approach in a Patient with Interrupted Inferior Vena Cava

Abstract: Percutaneous closure of secundum atrial septal defect (ASD II) is considered the treatment of choice in the majority of cases. Interrupted inferior vena cava with azygos continuation can make delivery of the occluder difficult or not possible. Transjugular, transhepatic approach or surgery can be the alternative. We present the case of a 53-year-old woman with ASD II and interrupted inferior vena cava, and describe successful atrial septal defect closure under transesophageal echocardiography guidance through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…In our experience, this technique is especially useful in the transcatheter closure of large ASDs in children and overcomes all the problems of device alignment mentioned earlier. There has been another report of a successful transcatheter closure of an ASD in a patient with IVC anomaly using the femoral route itself . That case differed from ours in that the patient had an IVC interruption with azygous continuation rather than an IVC obstruction, and the RA entry was via the azygous continuation.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our experience, this technique is especially useful in the transcatheter closure of large ASDs in children and overcomes all the problems of device alignment mentioned earlier. There has been another report of a successful transcatheter closure of an ASD in a patient with IVC anomaly using the femoral route itself . That case differed from ours in that the patient had an IVC interruption with azygous continuation rather than an IVC obstruction, and the RA entry was via the azygous continuation.…”
Section: Discussioncontrasting
confidence: 52%
“…The commonest anomaly encountered is interruption of the IVC, which makes it virtually impossible to deploy the device using the femoral route. Various techniques and other avenues of access have been used in such patients to ensure successful transcatheter closure []. We report a case of a large secundum ASD in a young 3‐year‐old girl who turned out to have a Chronic Budd–Chiari syndrome and in whom we were able to successfully deploy the ASD device using the femoral route itself.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach tends to be abandoned when interruption of the IVC is encountered, in favor of transjugular access [4,5] or transhepatic puncture [6][7][8][9][10][11]. There has only been one previous publication describing successful transfemoral device closure of a small ASD in a case of interrupted IVC in an adult [12]. Ours is the first report of successful percutaneous transfemoral closure of an ASD in a child with a large ASD and an interrupted IVC with azygous continuation to the SVC.…”
Section: Discussionmentioning
confidence: 98%
“…Several routes for closure of atrial septal defects in patients with interrupted IVC have been reported. [4][5][6][7][8] This anomaly can occasionally complicate transcatheter intervention by rendering more difficult the usual direct route from the femoral venous access. This has been overcome by use of several reported …”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Flosdorff et al reported a successful transfemoral closure in a 3-year-old boy with an 8x10-mm secundum ASD and interrupted IVC with azygos continuation. [4] The authors were the first to demonstrate that percutaneous closure of ASD via azygos continuation is practicable in children.…”
mentioning
confidence: 99%